La localisation des entreprises logistiques et le positionnement des régions urbaines nord-ouest européennes - Mathieu Strale (Belgeo)
Logistics is an economic sector that knows a strong growth, resulting from the current, flexible and globalised economic system based on multiple exchanges. However, its geography remains largely unknown because its development is recent and information sources are not very numerous. The study of the firms location may be a solution. It brings to light a space distribution polarized by the urban and transport centres, but with strong variations between the different branches of the logistics industry. The construction of a regional typology synthesizes these elements and makes it possible to integrate them into a broader perspective of economic geography, where metropolitan areas have a key function. Centred on these latter, a double decreasing gradient appears. It is based on the one hand on the density of activities and on the other hand on the type of logistics firms.